2024
DOI: 10.3389/fpubh.2024.1342800
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing death attitudes of medical students: a scoping review

Jingjing Tong,
Qian Liu,
Ying Liu
et al.

Abstract: AimTo summarize factors influencing death attitudes of medical students, help identify intervention targets, and design precision interventions for improving death attitudes of medical students.MethodsWeb of Science, PubMed, Embase, OVID, China National Knowledge Infrastructure, and Wanfang databases were searched. Retrieval time was from January 2012 to September 2023. Studies on factors influencing death attitudes of medical students were included.ResultsThirty-five studies were included in the final review.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
(97 reference statements)
0
0
0
Order By: Relevance
“…There is evidence that various factors, including cultural and religious background, influence medical students' attitudes towards death [42,47]. Our study has shown that attitudes towards death impact (future) physician's dealing with the dying patients.…”
Section: Limitations Of This Study and Suggestions For Further Researchmentioning
confidence: 60%
“…There is evidence that various factors, including cultural and religious background, influence medical students' attitudes towards death [42,47]. Our study has shown that attitudes towards death impact (future) physician's dealing with the dying patients.…”
Section: Limitations Of This Study and Suggestions For Further Researchmentioning
confidence: 60%